Liquidity Risk in Islamic Banking: Structural Challenges and Shariah-Compliant Mitigation Strategies - Al-Deek, Muhammad Youssef (Universitas Muhammadiyah Surakarta, 2025)
Liquidity management remains a critical challenge for Islamic banks due to their unique operational framework, which prohibits interest-based transactions and limits access to conventional monetary instruments. This study investigates the nature, causes, and effective mitigation strategies for liquidity risk within Islamic financial institutions. Adopting a descriptive-analytical approach, the research examines both internal and external factors contributing to liquidity imbalances such as maturity mismatches, sudden deposit withdrawals, underdeveloped secondary markets, and the absence of a Sharia-compliant lender of last resort. The findings reveal that Islamic banks face heightened liquidity pressures compared to conventional counterparts, primarily due to regulatory and structural constraints rooted in Islamic jurisprudence. To address these challenges, the study proposes a multi-pronged strategy: (1) strengthening interbank coordination among Islamic financial institutions, (2) expanding direct real-sector investments, (3) enhancing the use of Sharia-compliant instruments such as sukuk (Islamic bonds), and (4) activating short-term contracts like Salam and Istisna’ for efficient liquidity deployment. The paper concludes that effective liquidity management in Islamic banking requires not only robust internal governance but also supportive regulatory frameworks and deeper integration of Islamic capital markets. These measures are essential to ensure financial stability, protect depositor interests, and uphold the socio-economic objectives of Islamic finance.